1971
DOI: 10.1159/000468251
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Action on Rat Phosphate Metabolism

Abstract: Intravenous injection of radioactive phosphate and 300 to 900 Mmoles of LiCl was found (1) to increase radioactive phosphorus in muscle, liver, and brain, and (2) to decrease radioactive phosphorus in skull and decrease serum phosphate concentration. These findings may be secondary to the lithium action on carbohydrate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1973
1973
1986
1986

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…Furthermore, it was observed that lithium decreased the uptake of magnesium into bones. This de crease in bone uptake after lithium, has also been observed with respect to calcium (1) and phosphate (18); and the increase in serum magnesium is similar to the increase in serum calcium (1), whereas phosphate (18) is decreased after lithium administration.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Furthermore, it was observed that lithium decreased the uptake of magnesium into bones. This de crease in bone uptake after lithium, has also been observed with respect to calcium (1) and phosphate (18); and the increase in serum magnesium is similar to the increase in serum calcium (1), whereas phosphate (18) is decreased after lithium administration.…”
Section: Discussionsupporting
confidence: 65%
“…The lithium effect on carbohydrate metabolism is followed by an increased uptake of phosphate into muscle in vivo as well as in vitro, and a decrease in serum phosphate; also incorporation of phosphate into bone is decreased after lithium (18). In bones, the phosphate ions are electrically neutralized -primar ily by calcium ions, but also about half of the total body magnesium is deposited in the bones.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier (Plenge et al, 1971;Mellerup and Rafaelsen, 1975) we suggest that the changes in phosphate metabolism after lithium administration are secondary to a variety of changes in carbohydrate metabolism. The resulting uptake of phosphate into, especially, muscle and liver explains the decrease in serum phosphate, and is followed by decreased uptake or increased release of phosphate from the bones, which in turn may be accompanied by parallel changes in bone calcium and magnesium.…”
Section: Discussionsupporting
confidence: 58%
“…Animai experiments have shown that acute administration of lithium influenced calcium and magnesium metabolism {Mellerup et al, 1970; 1973), and that the observed changes may be secondary to the effect of lithium on phosphate and carbohydrate metabolism {Gotfredsen and Plenge et al, 1971 ;Mellerup and Rafaelsen, 1975). However, such initial changes may disappear during prolonged treatment, whereas other changes may be ob served only after lithium has been given for some time.…”
Section: Introductionmentioning
confidence: 99%
“…(Endocrinology 94: 915, 1974) HPHE significance and mechanisms responsible •*-for the reported decrease in serum inorganic phosphorus, increase in serum total calcium, and decrease in the incorporation of ( 45 Ca) and ( 32 P) into bone following the intraperitoneal injection of a single large dose of lithium chloride (LiCl) to a rat are not known (1,2). Calcitonin, parathyroid hormone, and renal function per se do not appear to be responsible for the observed changes since the changes occur in the absence of the kidneys and the thyroid, and parathyroid glands.…”
mentioning
confidence: 99%